Metformin treatment in young children with fragile X syndrome. Issue 11 (14th September 2019) - Biag, Hazel Maridith B.; Potter, Laura A.; Wilkins, Victoria; Afzal, Sumra; Rosvall, Alexis; Salcedo‐Arellano, Maria Jimena; Rajaratnam, Akash; Manzano‐Nunez, Ramiro; Schneider, Andrea; Tassone, Flora; Rivera, Susan M.; Hagerman, Randi J.
Abstract: Background: Metformin is a drug commonly used in individuals with type 2 diabetes, obesity, and impaired glucose tolerance. It has a strong safety profile in both children and adults. Studies utilizing the Drosophila model and knock out mouse model of fragile X syndrome (FXS) have found metformin to rescue memory, social novelty deficits, and neuroanatomical abnormalities. These studies provided preliminary evidence that metformin could be used as a targeted treatment for the cognitive and behavioral problems associated with FXS. Previously, a case series of children and adults with FXS treated with metformin demonstrated improvements in irritability, social responsiveness, language, and hyperactivity. Methods: Here, we present nine children with FXS between 2 and 7 years of age who were treated clinically with metformin and monitored for behavioral and metabolic changes. Results: Parent reports and developmental testing before and after metformin are presented. There were improvements in language development and behavior (such as lethargy and stereotypy) in most of the patients. Conclusion: These results support the need for a controlled trial of metformin in children with FXS under 7 years old whose brains are in a critical developmental window and thus may experience a greater degree of clinical benefit from metformin. Abstract : Studies utilizing the Drosophila model and knock out mouse model of fragile X syndrome (FXS) have found metformin to rescue memory, social novelty deficits, and neuroanatomical abnormalities. These studies provided preliminary evidence that metformin could be used as a targeted treatment for the cognitive and behavioral problems associated with FXS. Here, we present nine children with FXS between 2 and 7 years of age who were treated clinically with metformin and monitored for behavioral and metabolic changes.